Pengembangan Media Pembelajaran Big Book “Garuda Pancasila” untuk Meningkatkan Pemahaman Nilai Pancasila Siswa kelas 3 - Tessalonika Jesy Worang; Susan Noviaty Herienth Jacobus (Journal on Education, 2024)
Development (R&D). This model is implemented through 4D with 4 stages: 1) Define, 2) Design, 3) Develop, 4) Disseminate. The types of data applied are quantitative and qualitative data. Data was collected through interviews, questionnaires and tests. With research instruments in the form of interview guides, validation instruments which include validation instruments for content/material experts and validation instruments for learning media experts, this questionnaire has teacher and student response questionnaires to test the practicality of the product, as well as instruments for testing the effectiveness and effectiveness of the product from students. . Data were analyzed using descriptive statistical data analysis techniques. Quantitative data was obtained from a Likert scale score questionnaire and qualitative data was in the form of scores from validator suggestions. The results explain that the development of Big Book media in the validation stage got a score of 96% in the very good group, then in the validation stage the learning media design expert got a score of 62% in the very good category, after validation was applied the learning media design expert got a score of 76% in the category Good. In order to see the effectiveness of the Big Book learning process for increasing knowledge of Pancasila values, pre and post tests were applied to the sample and then applied through the Wilcoxon test and obtained sig. < 0.05 then there is a difference between the values. before and after applying the product. Testing via the Mann-Whitney test on sig. ∝= 0.05. The value is obtained from the hypothesis < 0.05, namely. 0.002 means that this big book learning media received a positive response from the teachers because the learning media can provide increased understanding of Pancasila values ​​for class III A students at SD Catholic 14 Manado.